Streptomyces sp. AC04842: Genomic Insights and Functional Expression of Its Latex Clearing Protein Genes (lcp1 and lcp2) When Cultivated With Natural and Vulcanized Rubber as the Sole Carbon Source - Basik, Ann Anni; Trakunjae, Chanaporn; Yeo, Tiong Chia; Sudesh, Kumar (Frontiers in Microbiology, 2022)
Rubber degrading Actinobacteria have been discovered and investigated since 1985. It is only recently that through advancement of genomic sequencing and molecular techniques that genes and pathways involved in rubber degradation are being revealed, however, the complete degradation pathway remains unknown. Streptomyces sp. AC04842 (JCM 34241) was discovered by screening at a Culture Collection Centre in Sarawak for Actinomycetes forming a clear zone on natural rubber latex agar. Streptomyces is a dominant and well-studied soil bacterium playing an important role in soil ecology including carbon recycling and biodegradation. Streptomyces sp. AC04842 draft genome (JADBHJ000000000) revealed the presence of 2 latex clearing protein (lcp) genes on its chromosome and is closely related to Streptomyces cellulosae. Under the Streptomyces genus, there are a total of 57 lcp genes deposited in NCBI. Only 1 lcp gene from Streptomyces sp. K30 has been characterized. Unlike Streptomyces sp. K30 which contained 1 lcp gene on its chromosome, Streptomyces sp. AC04842 contained 2-lcp genes on its chromosome. Streptomyces sp. AC04842 Lcp1 and Lcp2 amino acid sequences showed 46.13% and 69.11% similarity to Lcp of Streptomyces sp. K30 (AAR25849.1). Most rubber degrading strains were known to harbour 1 lcp gene and only recently 2 to 3-Lcp homologs have been reported. Several studies have shown that Lcp-homologs expression increased in the presence of rubber. To study the expression of the Lcp1 and Lcp2 of Streptomyces sp. AC04842, the strain was incubated in different types of rubber as the sole carbon source. In general, Lcp1 was highly expressed, while Lcp2 expression was upregulated in the presence of vulcanized rubber. Mixtures of natural and vulcanized rubber did not further increase the expression of both Lcp compared to the presence of a specific rubber type. Exploration of Lcp-homologs and their function in degrading different types of rubber would be of interest.